PENGARUH PROMOSI DAN FASILITAS TERHADAP MINAT BELI KONSUMEN (Studi Kasus Perumahan Villa Bunga Arengka PT. Adhi Karya Persada Nusantara Pekanbaru) - Febrina, Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
In an increasingly competitive level, companies must be able to face competitors who offer similar products. Realizing that the company PT. Adhi Karya Persada Nusantara has been prepared by conducting promotions and preparing adequate facilities to meet the needs and challenges needed by the people of Pekanbaru city. This study aims to determine the implementation of promotions and facilities offered, to determine consumer buying interest, and to determine the effect of promotion and facilities offered on consumer buying interest in Villa Bunga Arengka housing type 70 at PT. Adhi Karya Persada Nusantara. This research is descriptive quantitative with statistical calculation. Statistical analysis used in this research is multiple linear regression. Population in this research is resident of Villa Bunga Arengka type 70 house as much as 150 KK. The sample used in this study taken 50% of the total population is set as many as 70 respondents. The results showed that the promotion of Villa Bunga Arengka housing type 70 at PT. Adhi Karya Persada Nusantara is in the category